Between theater and anthropology - Schechner, Richard 1934- (University of Pennsylvania, 1985)
"Fascinating for anyone seriously interested in human behavior, full of ideas that lead us to reexamine our thinking about all performances, from the most dramatic to the most seemingly trivial."ÑNew York Times.\In performances by Euro-Americans, Afro-Americans, Native Americans, and Asians, Richard Schechner has examined carefully the details of performative behavior and has developed models of the performance process useful not only to persons in the arts but to anthropologists, play theorists, and others fascinated (but perhaps terrified) by the multichannel realities of the postmodern world.\Schechner argues that in failing to see the structure of the whole theatrical process, anthropologists in particular have neglected close analogies between performance behavior and ritual. The way performances are createdÑin training, workshops, and rehearsalsÑis the key paradigm for social process.